Educational interventions to empower nursing home residents: a systematic literature review - Schoberer D; Leino-Kilpi H; Breimaier H; Halfons R; Lohrmain C (New Zealand, 2022)
Individually tailored, interactive, continuously applied, and structured educational strategies, including motivational and encouraging techniques, are promising interventions that can help nursing home residents become more empowered. Empowering strategies used by nurses can support residents in their growth and facilitate their self-determination. Further research on the empowerment of residents using empowerment scales is needed.